PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SYIFA HARAPAN HIDUP SUKABUMI - Khoerunnisa Khoerunnisa; Kadarmanta, R.A. (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the determinant factors that influence employee performance, both internal factors (workload) and external factors (work environment). In addition, this study also examines the effect of these two factors on employee performance, both partially and simultaneously, to determine the extent to which workload and work environment play a role in improving employee effectiveness. The research was conducted at PT Syifa Harapan Hidup, a company engaged in the health services sector, using a quantitative research method. Data were collected through questionnaires distributed to respondents, while the data analysis techniques used included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing (t-test and F-test). Based on the results of the analysis, it was found that workload partially has a positive and significant effect on employee performance with a coefficient of determination of 41.8%, as evidenced by the t-test results (t_count 11.047 > t_table 2.010). The work environment also partially has a positive and significant effect on employee performance with a coefficient of determination of 29.1% (t_count 8.259 > t_table 2.010). Simultaneously, workload and work environment have a positive and significant effect on employee performance, with a coefficient of determination of 87.6% and F-test results showing F_count 166.177 > F_table 3.195. These results indicate that the better the workload management and the more conducive the work environment created by the company, the higher the employee performance will be